2017
DOI: 10.1136/jech-2016-208511
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and offspring antisocial behaviour: findings from a longitudinal investigation of discordant siblings

Abstract: Findings are consistent with a small-to-moderate causal effect of MSP on adolescent and adult antisocial behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…That study was a subsample (sample size ranged from 1,883 to 3,447 depending on the outcome) of a much larger study (n ¼ 52,919), which reported results inconsistent with a causal effect of maternal smoking during pregnancy on childhood conduct problems measured at age 7 (Gilman, Gardener, et al, 2008). In the study by Paradis et al (2017), the within-family effect tended to be larger than the between-family effect for the six offspring antisocial behavior outcomes examined. However, the confidence intervals for the within-family effects were very wide, and results fluctuated depending on the outcome variable and how it was defined.…”
Section: Maternal Smoking During Pregnancy and Offspring Conduct Probmentioning
confidence: 95%
“…That study was a subsample (sample size ranged from 1,883 to 3,447 depending on the outcome) of a much larger study (n ¼ 52,919), which reported results inconsistent with a causal effect of maternal smoking during pregnancy on childhood conduct problems measured at age 7 (Gilman, Gardener, et al, 2008). In the study by Paradis et al (2017), the within-family effect tended to be larger than the between-family effect for the six offspring antisocial behavior outcomes examined. However, the confidence intervals for the within-family effects were very wide, and results fluctuated depending on the outcome variable and how it was defined.…”
Section: Maternal Smoking During Pregnancy and Offspring Conduct Probmentioning
confidence: 95%
“…Though the figure was lower, active or passive tobacco smoke exposure during pregnancy has adverse health effects on the fetus, as well as the mother. The adverse health effect of cigarette smoke on the fetus includes, an increased risk of strabismus in the offspring [71], clubfoot [72], low birth weight for gestational age (LBWGA), low birth weight, preterm births (28,29), increased odds of elevated levels of antisocial behaviors during adolescence and adulthood, as well as violent and nonviolent outcomes [73], an increased risk of wheeze in children [74], and almost 3 times increased risk of congenital heart defects [75]. Moreover, tobacco smoke during pregnancy increases the prevalence of depressive symptoms during pregnancy [76].…”
Section: Plos Onementioning
confidence: 99%
“…These findings point to the existence of a small direct link between MDSP and childhood and adolescent aggression that is remarkably consistent cross-culturally. Further evidence for and against our hypothesis can come from within-family studies, but to date these have found inconsistent results (D'Onofrio et al , 2010; Kuja-Halkola et al , 2014; Estabrook et al , 2016; Marceau et al , 2018; Paradis et al , 2017; Quinn et al , 2017).…”
Section: Discussionmentioning
confidence: 78%
“…Marceau et al (2018) found that the effect of MSDP on variation in offspring's ADHD remained significant even after accounting for within-family factors and suggested that the effects of MSDP may be best captured when hyperactivity and impulsivity are assessed across the population rather than when considering severe diagnosis or symptoms count. Two further investigations supported a direct link between MSDP and offspring antisocial behaviour (Paradis et al , 2017) and conduct disorder (Estabrook et al , 2016) after accounting for within-family confounds.…”
Section: Introductionmentioning
confidence: 91%